Zdrav življenjski slog starih ljudi - Cesar, Katarina (Socialno delo, 2021)
The challenge of a long-lived society is how to provide such support and help that we will be able to age as healthily and independently as possible. The article shows what are the important factors of quality aging, with special emphasis on the importance of a healthy lifestyle and within this, sports and recreational activity and social networks. A quantitative study on a non-randomized convenience sample of 209 people over the age of 65 conducted by a survey found that almost all surveyed older people estimate that they can maintain a healthy lifestyle and that their lives are most affected by age. Almost half of them are engaged in exercise three times a week or more, but more frequent activity is not associated with better health. More than half have three or more people available to whom they can turn for help, and they also better assess their health. However, self-assessment of health is not related to the frequency of socializing. The more educated are more likely to believe that they can influence their health through their lifestyle. Familiarity with activities and events for a healthy lifestyle, however, is weak. To promote a healthy lifestyle, measures are needed at all levels – micro, mezzo and macro.
Keywords: demografske spremembe; demografsko staranje; demographic change; health; kakovostno staranje; population aging; quality aging; zdravje